Meeting Micronutrient Requirements for Health and Development: An Update - Alam, M Jahangir; Mobarak, R; Alam, HS Kamrul; Haque, M Shafiul; Tayab, M Abu (Bangladesh Journal of Child Health, 2012)
DOI: http://dx.doi.org/10.3329/bjch.v36i1.13035 Bangladesh J Child Health 2012; Vol 36 (1): 36-45